The Scotland and Newcastle epidemiological study of Hodgkin's disease: impact of histopathological review and EBV status on incidence estimates. Issue 11 (4th November 2003) - Jarrett, R F; Krajewski, A S; Angus, B; Freeland, J; Taylor, P R; Taylor, G M; Alexander, F E
Abstract : Aims: The epidemiological and pathological features of Hodgkin lymphoma (HL) are complex. The Epstein-Barr virus (EBV) is consistently associated with a proportion of cases, and these cases are thought to represent a distinct aetiological subgroup of HL. The aim of the present analysis was to determine the age and sex specific incidence of EBV associated and non-associated HL, analysed separately, using data derived from a population based study–the Scotland and Newcastle epidemiological study of Hodgkin's disease (SNEHD). This study also provided a unique opportunity to evaluate accuracy in the current diagnosis and classification of HL. Methods: SNEHD analysed consecutive cases of HL diagnosed in the study area between 1993 and 1997. Diagnostic biopsy material was retrieved, EBV status of tumours was determined, and histological review was performed. Results: In total, 622 cases were eligible for the study, and EBV studies and histopathological review were performed on biopsy material from 537 and 549 cases, respectively. Accuracy in the overall diagnosis of HL and classification of nodular sclerosis HL was good, but diagnosis of HL in the elderly and classification of other subtypes was less reliable. One third of classic HL cases were EBV associated, and age specific incidence curves for EBV associated and non-associated cases were distinct. Conclusions: Comparison of age specific incidence curves for EBV associated and non-associated HL supports the hypothesis that these are two distinct aetiological entities. Accuracy in the diagnosis of HL is generally good, but certain subgroups of cases continue to present diagnostic difficulties.